1988
DOI: 10.1172/jci113829
|View full text |Cite
|
Sign up to set email alerts
|

Sterol synthesis and low density lipoprotein clearance in vivo in the pregnant rat, placenta, and fetus. Sources for tissue cholesterol during fetal development.

Abstract: Whereas the greatest relative increase in body mass occurs during the third trimester of fetal life, the source of the cholesterol that supports this growth is uncertain. These studies used I3Hlwater and "2'I-cellobiose-labeled low density lipoproteins to quantitate absolute rates of cholesterol acquisition in vivo by the fetus of the rat. Preliminary studies demonstrated that 13Hlwater administered intravenously to the mother rapidly equilibrated with the body pool of water in the fetus and that 22-,ug atoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
53
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(57 citation statements)
references
References 30 publications
4
53
0
Order By: Relevance
“…The high cholesterol synthesis may be related to the needs of a still-growing organism. Third, in the later stages of pregnancy, when circulating estrogen levels reach the highest point (26), there was a dramatic decrease of expression of all enzymes, possibly because at day 17 of pregnancy, the fetus acquires the ability to produce its own cholesterol (27). Finally, and most relevantly, in the absence of a cycle due to age or surgical menopause, expression of most of the genes studied was not oscillatory and was generally set to accumulate the mRNAs at levels significantly higher than those at proestrus.…”
Section: Discussionmentioning
confidence: 99%
“…The high cholesterol synthesis may be related to the needs of a still-growing organism. Third, in the later stages of pregnancy, when circulating estrogen levels reach the highest point (26), there was a dramatic decrease of expression of all enzymes, possibly because at day 17 of pregnancy, the fetus acquires the ability to produce its own cholesterol (27). Finally, and most relevantly, in the absence of a cycle due to age or surgical menopause, expression of most of the genes studied was not oscillatory and was generally set to accumulate the mRNAs at levels significantly higher than those at proestrus.…”
Section: Discussionmentioning
confidence: 99%
“…As in the adult, this cholesterol is supplied by either de novo synthesis within the fetal compartment or by transfer from the maternal compartment to the fetus through uptake of cholesterol carried in lipoproteins. Previous studies have shown that sterol synthesis is markedly increased in the developing fetus including a preimplantation embryo (27)(28)(29). In addition, transport of maternal LDL and HDL to the fetal yolk sac is drastically increased (30).…”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that the placental system is too immature to fully compensate for the complete deficiency of the de novo cholesterol synthesis around this developmental stage. Belknap and Dietschy (27) have shown that the de novo cholesterol synthesis remains highly active during the whole midgestational period and that the contents of newly synthesized sterols are maximal at E17 in the rat fetus. Similar failure to catch up with the increasing demand may underlie the lethality of mice lacking apoB (11,12,39) or microsomal triglyceride transfer protein (13), because both mutants die at the same developmental stage.…”
Section: Discussionmentioning
confidence: 99%
“…At 11.5 days post-conception (dpc), studies were performed; hamsters have a gestational period of 15.5 days. [31,33].…”
Section: Animals and Dietsmentioning
confidence: 99%